Classification of Bangladeshi soil texture using convolutional neural network - Raj, Hafiz Mohiuddin; Shahreen, Sazia; Shah, Muntaha Binte; Evan, Syed Washinur Ashraf; Abdullah, Juhayer (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.